Potency of Solar Energy Applications in Indonesia - Handayani, Noer Abyor; Ariyanti, Dessy (Center of Biomass & Renewable Energy, Diponegoro University, 2012)
Currently, 80% of conventional energy is used to fulfill general public's needs andindustries. The depletion of oil and gas reserves and rapid growth in conventional energyconsumption have continuously forced us to discover renewable energy sources, like solar, wind,biomass, and hydropower, to support economic development in the future. Solar energy travels at aspeed of 186,000 miles per second. Only a small part of the radiant energy that the sun emits intospace ever reaches the Earth, but that is more than enough to supply all our energy demand.Indonesia is a tropical country and located in the equator line, so it has an abundant potential ofsolar energy. Most of Indonesian area get enough intensity of solar radiation with the average dailyradiation around 4 kWh/m2. Basically, the solar systems use solar collectors and concentrators forcollecting, storing, and using solar radiation to be applied for the benefit of domestics, commercials,and industrials. Common applications for solar thermal energy used in industry are the SWHs, solardryers, space heating, cooling systems and water desalination.